Immunomodulatory nanodiamond aggregate-based platform for the treatment of rheumatoid arthritis - Pentecost, Amanda; Kim, Min Ju; Jeon, Sangmin; Ko, Young Ji; Kwon, Ick Chan; Gogotsi, Yury; Kim, Kwangmeyung; Spiller, Kara L. (OXFORD UNIV PRESS, 2019)
We previously demonstrated that octadecylamine-functionalized nanodiamond (ND-ODA) and dexamethasone (Dex)-adsorbed ND-ODA (ND-ODA-Dex) promoted anti-inflammatory and pro-regenerative behavior in human macrophages in vitro. In this study, we performed a pilot study to investigate if these immunomodulatory effects translate when used as a treatment for rheumatoid arthritis in mice. Following local injection in limbs of mice with collagen type II-induced arthritis, microcomputed tomography showed that mice treated with a low dose of ND-ODA and ND-ODA-Dex did not experience bone loss to the levels observed in non-treated arthritic controls. A low dose of ND-ODA and ND-ODA-Dex also reduced macrophage infiltration and expression of pro-inflammatory mediators iNOS and tumor necrosis factor-alpha compared to the arthritic control, while a high dose of ND-ODA increased expression of these markers. Overall, these results suggest that ND-ODA may be useful as an inherently immunomodulatory platform, and support the need for an in-depth study, especially with respect to the effects of dose.
Keywords: SYNOVIAL TISSUE MACROPHAGE; NECROSIS-FACTOR-ALPHA; PARTICLE-SIZE; DEXAMETHASONE; ACTIVATION; RECEPTOR; GLUCOCORTICOIDS; INTERLEUKIN-10; NANOPARTICLES; PHAGOCYTOSIS